Carta del Director Diciembre 2011 - Martínez Ventura, Jaime Edwin (Revista Policía y Seguridad Pública, 2014)
DOI: http://dx.doi.org/10.5377/rpsp.v1i1.1380 Revista Policía y Seguridad Pública 1(1) 2011: 13-14